Sustainability of carbon: research on the impact of digital technology development on carbon equity - Zhang, Liyao; Wang, Yijing; Geng, Yingying; Li, Chaoyang (Frontiers in Environmental Science, 2025)
Actively leveraging the advantages of digital technology in promoting carbon equity development has provided a feasible solution for achieving ecological common prosperity. Based on provincial panel data from China spanning 2013 to 2023, this study investigates the intricate impacts of digital technologies on carbon equity utilizing fixed effects, mediation, and moderating models. The benchmark regression results indicate that digital technology has a significant positive effect on carbon equity, with heterogeneous effects across regions: “middle region > western region > eastern region”. The mechanism effect study indicates that digital technology can indirectly promote the realization of carbon equity by reducing energy intensity and optimizing the energy structure. The moderating effect study reveals that both energy intensity and energy structure negatively moderate the relationship between digital technology on carbon equity. The research findings extend the theoretical boundaries of how digital technology can contribute to the construction of carbon equity, while providing certain reference value for the implementation of ecological civilization construction and the high-quality development of the “carbon neutrality” strategy in a manner that suits local conditions.